CERTAIN PROPERTIES OF MITTAG-LEFFLER FUNCTION WITH ARGUMENT \(x^{α}\), α > 0 - Prajapati, Jyotindra C. (Italian Journal of Pure and Applied Mathematics, 2013)
In this paper, author discusses some interesting properties such as Composition property, Power series expansion, Inverse property, Increasing property, Positivity and Limiting case of Mittag-Leffler function with argument xα, α > 0.